Analisis Kinerja Pegawai Tata Usaha dalam Memberikan Pelayanan Administrasi di SMK Cerdas Murni Tembung - Shelvia Permatasari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study used a descriptive qualitative method, with the principal, vocational studies teacher as well as the deputy head of student affairs, administrative staff and students of SMK Cerdas Murni as the research subjects. Data were collected through interviews, observations, and document studies. Then it was analyzed using Farida Nugrahani's Interactive Analysis Model (2014: 173), and tested for validity using the triangulation method. The results showed that the performance of administrative staff in providing student administration services, and correspondence and archival administration at SMK Cerdas Murni was considered quite good. This is evident from the timely completion of tasks, the existence of discipline, a sense of responsibility, the ability to cooperate and communicate well. Supporting factors for performance are the ability of administrative staff, reward and punishment, facilities and work atmosphere, and good relationships with coworkers and superiors. Conversely, the inhibiting factors are the lack of technical competence and damage to work tools. And the steps in streamlining administrative services at SMK Cerdas Murni are, hastening the completion of tasks, conducting discussions with the principal and teachers, attending workshops to improve competence and keep up with existing developments.